Answer:
is the solution to the system of equations.
Explanation:
Given the system of equations as:
![y= (1)/(2)x-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/uxkldf76n7vg28gk9vp30uoi7ucof95705.png)
and
![x =-4](https://img.qammunity.org/2021/formulas/mathematics/high-school/di9ptx3g2zvonp0zdjymsrssducz61pnmw.png)
To find:
The solution to the system of equations = ?
Solution:
Here, we are given two equations and two variables i.e.
and
.
So, we can solve the system of equations for the values of
and
.
Let us first consider the 2nd equation.
we already have the value of
.
Now, let us put the value of
in the 1st equation to find the value of
.
![y= (1)/(2)x-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/uxkldf76n7vg28gk9vp30uoi7ucof95705.png)
![\Rightarrow y= (1)/(2)* (-4)-6\\\Rightarrow y= -(1)/(2)* 4-6\\\Rightarrow y= -2-6\\\Rightarrow \bold{y =-8}](https://img.qammunity.org/2021/formulas/mathematics/high-school/5t75kg0pwm2ma9z8uhonmtrdphanx9bzy9.png)
So, the solution to the system of equations is:
![x = -4, y =-8](https://img.qammunity.org/2021/formulas/mathematics/high-school/fyk1z3oqvzrgrjckpktsr67w7y125fr5mp.png)